Effect of new coupling agent based on Coconut oil on mechanical properties, swelling behavior and morphology of Silica filled Polypropylene composites - Izyan Iryani Mohd Yazid (Universiti Malaysia Perlis, 2008)
The suitability of using coconut oil coupling agent (COCA) as a new coupling agent in polypropylene (PP) composites was studied. As compariosn, maleic anhydride polypropylene (MAPP) was used in silica filled PP composites. The coupling agent was prepared in the laboratory and it was verified that COCA have higher reactivity toward PP chains. The incorporation of coconut oil coupling agent (COCA) in silica filled PP composites give positive effect by improved tensile strength, elongation at break (Eb) and Young’s modulus but reduced the water absorption resistance. Micrographs of tensile fracture surfaces of silica filled PP composites exhibit that silica was covered by PP matrix as a result of better adhesion due to the presence of COCA or MAPP compared to the similar PP composites but without coupling agent.